The relationship between the use of the tiktok application and the learning interests of students of The Ende Nursing D-III Study Program - Syaputra Artama; Yustina Pacifica Maria Paschalia; Yohanes Nipa; Maria Yelmiana Panda; Odelberta Natalya Wale (Institute of Computer Science (IOCS), 2023)
Tiktok application media is a medium of entertainment and information attracting many people today, so it is not surprising that people in Indonesia, including students, use the application a lot. Some phenomema and all the information available on the application can have a positive or negative impact on its users. The increasing development of technology and the emergence of social media applications on the use of mobile phones are indicated to be able to influence students' habits in daily activities. This study aims to determine the relationship between the use of the Tiktok application and the learning interests of students of the D-III Nursing Study Program, Ende Poltekkes, Ministry of Health, Kupang. This research uses a descriptive quantitative correlation research method with a cross sectional study approach with a total sample of 50 students. The results of the study obtained that there was no relationship between the use of the Tiktok online application and student interest in learning with a p value = 0.443 (p>0.05). Interest in learning can be influenced by several factors, for the use of the Tiktok application in the student environment can have a positive or negative impact on life and activities including in the learning process of each student.